PENGARUH PENDIDIKAN KESEHATAN DENGAN VIDEO EDUKASI TENTAG BULLYING TEHADAP PERILAKU BULLYING PADA ANAK DI SD PUJOKUSUMAN 1 YOGYAKARTA - Firna Yolanda, Gani Apriningtyas Budiyati (AKPER Pemkab Purworejo, 2020)
Bullying behavior is the actions or behaviors in which the abuse of force is carried out by the child both physically and verbally. Bullying behavior have the negative impact to the children if not treat immediately. The school is a second home for school aged children which have the information about billying behavior. With the using viseo is the true media to the student in give the health education. Objective: to find out the effect of health education with educational videos about bullying on bullying behavior in children in elementary school Pujokusuman 1 Yogyakarta. Method: This type of research uses a Experiment research design with one group pre-post test design. The sampling technique used total sampling with a total of 60 students in elementary school Pujokusuman 1 Yogyakarta. The data analysis technique used a Wilcoxon Signed Rank Test. The research instruments used the kuesioner sheet of bullying behavior and educational videos about bullying. Results: The results showed that before being given health education about bullying behavior in the majority of children in the medium category as an many as 49 respondents (81%) and after being given health education about bullying behavior in the majority of children werw in the low category as many as 52 respondents (86,7%). Conclusion:there is have an effect before and after of providing health educational with educational videos about bullying on bullying behavior in elementary school Pujokusuman 1 Yogyakarta with the p value = 0,000 (<0,05)